Domains of Archean mantle lithosphere deciphered by seismic anisotropy – inferences from the LAPNET array in northern Fennoscandia - Plomerová, J.; Vecsey, L.; Babuška, V.; LAPNET Working Group (Solid Earth, 2011)
An international LAPNET array (2007–2009, http://www.oulu.fi/sgo-oty/lapnet) of the POLENET/LAPNET sub-project of the POLENET-IPY consortium, related to seismic and geodetic studies in the Arctic regions, consisted of about 60 broadband seismic stations located on the territory of northern Finland and adjacent parts of Sweden, Norway and Russia. We analyze relative P-wave travel-time deviations evaluated for a subset of 90 teleseismic events recorded by the LAPNET array and show examples of lateral variations of shear-wave splitting to demonstrate variability of fabrics of the Archean mantle lithosphere. The initial results clearly demonstrate the Archean mantle lithosphere consists of domains with consistent fabrics reflecting fossil anisotropic structures. 3-D self-consistent anisotropic models with inclined symmetry axes accommodate two independent sets of body-wave anisotropic observations. Individual domains are delimited by boundaries (sutures), where the anisotropic parameters change. The results obtained from the LAPNET array fill a gap in structural studies of the upper mantle beneath northern Fennoscandia.